Interação mãe-bebê e uso de chupeta no contexto do nascimento pré-termo: um estudo com base na Teoria Bioecológica - DADALTO, Elâine Cristina Vargas; ROSA, Edinete Maria (Estudos de Psicologia (Campinas), 2023)
The objective of this study was to evaluate mothers of preterm infants discharged from Neonatal Intensive Care Units with regard to the quality of Proximal Processes and use of pacifier during the first two years. The longitudinal design used was based on the Bioecological Theory of Human Development. Twelve mothers were interviewed at five different times; (during hospital stay and at 6, 12, 18, and 24 months after birth). Two groups were formed: Group A (n = 6), mothers who introduced a pacifier during the first two years of life, and Group B (n = 6), mothers who did not introduce this habit. Proximal Processes were more effective for mothers with higher education level and better economic situation, without interference of pacifier. According to the mothers who controlled pacifier use, which was most evident during sleep, it did not make any difference in terms of contributing to the Proximal Processes. The unrestricted use of pacifier helped soothing a crying baby, freeing the mother to engage in other tasks. In conclusion, it can be said that in this situation a pacifier inhibits Proximal Processes